META-ANALISIS PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP METAKOGNISI SISWA - Nishfiya Ramdoniati (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2021)
Abstract: The article describes meta-analysis result of Problem Based Learning (PBL) model to improve student’s metacognition. The meta-analysis method in this study is based on Hunter Schmidt calculations. The unit of analysis in this study are written documents about PBL model research on metacognition in the form of article journal that are taken provosive sampling based on conformity with the research theme. The sample in this study amounted to 850 students. This study was found that there are the impact of problem based learning model on metacognition with the value of effect size is 0.56 and the confidence interval is 0.09 to 1.03. Futher, the impact of incorrect sampling is relatively small at 1.23%.